The Role of Indigenous Knowledge Practices Within Transformative Reconciliation - Kelly, Vicki; Rosehart, Paula (Journal of the Canadian Association for Curriculum Studies, 2020)
This métissage explores scholarly relations among local Indigenous communities, school districts, teacher-learners and Simon Fraser University’s graduate diploma program titled Indigenous Education: Education for Reconciliation. Through our collective attending to the role of Indigenous knowledge practices and making within transformative reconciliation, a powerful resurgence of Indigenous ways of knowing and being emerged. This resurgence came about through participatory pedagogies of making and through the sharing of Indigenous knowledges, cultural practices, ceremony and language revitalization. The focus on Indigenous knowledge practices, circle processes and artmaking, as well as Indigenous worldviews, knowledges and perspectives, provided an enactment of rigorous resurgence and transformative reconciliation (Ash et al., 2018). Opportunities to be involved in Indigenous making and land practice with Indigenous Knowledge Holders provided occasions for teacher-learners to embody and embed Indigenous pedagogies and “two-eyed seeing” (Bartlett et al., 2012) within their educational practice. Throughout the program, teacher-learners were invited into Indigenous making, creative and critical conversations, exploring circle pedagogies, participatory processes, place-based explorations and intercultural dialogues with Indigenous Knowledge Holders and Elders. The teachers acknowledged and experienced Indigenous protocols and ceremonies, and they actively explored Indigenous teachings through Indigenous participatory pedagogies. An emphasis was placed on creating authentic Indigenous-learning pathways and to do so in relation to knowledge practices within a particular place, peoples and their unique cultural ecology. This Indigenous Métissage (Donald, 2012) weaves together narrative threads into a story of collaboration between teacher-learners and Knowledge Holders. They stand as a family stands, together to share and give witness to the profound learnings that have emerged from the journey.